Human factors methods for improving performance in the process industries - Crowl, Daniel A.; Attwood, Dennis A. (CCPS, Center for Chemical Process Safety ; Wiley-Interscience, 2007)
This book provides guidance for managers and plant engineering staff on specific, practical techniques and tools for addressing forty different human factors issues impacting process safety. Human factors incidents can result in injury and death, damage to the environment, fines, and business losses due to ruined batches, off-spec products, unplanned shutdowns, and other adverse effects. Prevention of these incidents increases productivity and profits.